Analisis Kepuasan Pengguna Telemedisin Di Jabodetabek Tahun 2023 - Dwiyanti, Erliyana; Umniyatun, Yuyun; Veruswati, Meita; A’yunin, Elia Nur (JURNAL PENDIDIKAN KESEHATAN, 2024)
Telemedicine serviceis a digital health service for patients with mild symptoms to conduct consultations and other services. Quality of serviceis a solution to health problems that must be measured to determineit ssuccess. This study aims to determine the quality of telemedicine services related to user satisfaction in Jabodetabek. The type of research used is quantitative with a cross-sectional design. Data was collected in November – December 2023 with a sampl e f 123 respondents. Data analysis used univariate and bivariate, while bivariate analysis was carried out using the normality test and Spearman rank test. The results found that as many as 89.4% of respondents were satisfied with telemedicine services. All variables have a significant relationship with telemedicine service user satisfaction with a moderate positive correlation, namely responsiveness (Pvalue = 0.000; r = 0.584), reliability (Pvalue = = 0,000 ; r = 0,536), assurance (Pvalue = 0.000 ; r = 0.492), empathy (Pvalue = 0.000 ; r = 0.424), and price variables with lowand positive correlation (Pvalue = 0.020 ; r = 0.209).